2020
DOI: 10.3390/nu12082440
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae and Caffeine Implications on the Eukaryotic Cell

Abstract: Caffeine–a methylxanthine analogue of the purine bases adenine and guanine–is by far the most consumed neuro-stimulant, being the active principle of widely consumed beverages such as coffee, tea, hot chocolate, and cola. While the best-known action of caffeine is to prevent sleepiness by blocking the adenosine receptors, caffeine exerts a pleiotropic effect on cells, which lead to the activation or inhibition of various cell integrity pathways. The aim of this review is to present the main studies set to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 161 publications
0
28
0
Order By: Relevance
“…The detergent SDS disrupts the plasma membrane, whereas CFW and Congo Red interfere with the synthesis of cell wall polysaccharides ( Elorza et al 1983 ; Wood and Fulcher 1983 ; Dichtl et al 2016 ; Liu et al 2021 ). Caffeine has a variety of targets in fungi including target of rapamycin (TOR) signaling and components of the CWI pathway ( Ruta and Farcasanu 2020 ). The grx4Δ mutants exhibited increased sensitivity to SDS, caffeine and CFW indicating that Grx4 is required for membrane and CWI; the Grx4 reconstituted strain restored growth to the WT level ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detergent SDS disrupts the plasma membrane, whereas CFW and Congo Red interfere with the synthesis of cell wall polysaccharides ( Elorza et al 1983 ; Wood and Fulcher 1983 ; Dichtl et al 2016 ; Liu et al 2021 ). Caffeine has a variety of targets in fungi including target of rapamycin (TOR) signaling and components of the CWI pathway ( Ruta and Farcasanu 2020 ). The grx4Δ mutants exhibited increased sensitivity to SDS, caffeine and CFW indicating that Grx4 is required for membrane and CWI; the Grx4 reconstituted strain restored growth to the WT level ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar pattern was detected in the grx4Δ mutant strain with a somewhat weaker signal at 30 min of caffeine treatment, and an even weaker signal at 120 and 150 min. It is known that caffeine has additional influences on cellular functions beyond an impact on the CWI pathway ( Ruta and Farcasanu 2020 ). A different pattern of phosphorylation was observed upon treatment with SDS ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Caffeine has multiple effects on eukaryotic cells. Although it is a specific inhibitor of TOR1 kinase, it also triggers ERAD mediated apoptosis (31). It also has a dramatic effect on DNA repair, cell wall integrity, and telomerase activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular events that activate autophagy are misfolded protein accumulations and damaged or dysfunctional cell components. Extracellular factors that activate autophagy are different chemicals and environmental cues such as amino acid starvation and nitrogen limitations (31,32). Autophagy processes can be classified into different sub-groups depending on reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Ruta and Farcasanu reviewed the studies evaluating the molecular mechanisms of action of caffeine in Saccharomyces cerevisiae as a simple model of eukaryotic cell. In addition to its three well-known mechanisms, namely intracellular mobilization of calcium, inhibition of phosphodiesterases and antagonism of adenosine receptors, the studies performed in this yeast model have confirmed that the pleiotropic effects of caffeine involve also key molecular mechanisms related with DNA repair mechanisms, cancer, and aging [ 20 ]. In contrast, Kolb et al reviewed the mechanisms that might contribute to explain the beneficial effects of habitual coffee consumption on health.…”
mentioning
confidence: 86%